2011
DOI: 10.1007/s12015-011-9237-7
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells in Tooth Tissue Regeneration—Challenges and Limitations

Abstract: The accelerated pace of research in the stem cell field in recent decades and the accumulated body of knowledge has spurred the interest in potential clinical applications of stem cells in all branches of medicine including regenerative dentistry. In humans, embryonic and adult stem cells are two major groups of cells that can serve as a donor source in tissue engineering strategies based on ex-vivo cellular expansion. It has been shown that adult stem cell populations are present in all examined living tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 113 publications
(130 reference statements)
0
17
0
1
Order By: Relevance
“…The current knowledge suggests that over 300 types of genes, 100 varieties of growth and differentiation factors, and multiple relevant signaling molecules are involved in the dynamic process of tooth development. During this process, the spectrum and concentration of a large number of substances change continuously until the completion of tooth eruption is achieved [26, 35]. In addition, tooth germ cell-conditioned medium may be one of the best choices for this culture condition, as previous studies have suggested that the mixture of soluble factors secreted from the epithelial and mesenchymal cells of developing tooth germs creates an odontogenic microenvironment that could guide the differentiation of odontogenic and nonodontogenic cells along the odontoblast lineage [20, 26, 36].…”
Section: Discussionmentioning
confidence: 99%
“…The current knowledge suggests that over 300 types of genes, 100 varieties of growth and differentiation factors, and multiple relevant signaling molecules are involved in the dynamic process of tooth development. During this process, the spectrum and concentration of a large number of substances change continuously until the completion of tooth eruption is achieved [26, 35]. In addition, tooth germ cell-conditioned medium may be one of the best choices for this culture condition, as previous studies have suggested that the mixture of soluble factors secreted from the epithelial and mesenchymal cells of developing tooth germs creates an odontogenic microenvironment that could guide the differentiation of odontogenic and nonodontogenic cells along the odontoblast lineage [20, 26, 36].…”
Section: Discussionmentioning
confidence: 99%
“…The main stem cell populations of NDMSCs include BMSCs, 20 MSCs from peripheral nerve-associated glia, adipose tissue-derived MSCs (ADSCs), and induced pluripotent stem cells (iPSCs) 39, 40, 41, 42. BMSCs exhibit capacity for adipogenic and osteogenic differentiation 43 .…”
Section: Tooth Development and Dental Stem Cellsmentioning
confidence: 99%
“…The regenerative response of teeth to damage and structural degeneration are diverse and compartment-dependent, since teeth, as complex structures, harbour both living (periodontal ligament, cementum, pulp) and acellular (enamel, dentine) tissues. Of all the dental structures, only enamel is incapable of regenerating its original structure, while the remaining tissues possess that capacity in varying degrees, dependent on multiple factors (Inanç & Elçin, 2011). The dental pulp plays a major role in tooth regeneration after injury, by participating in a process called reparative dentinogenesis.…”
Section: Role Of Dpscs In Regenerative Medicinementioning
confidence: 99%